Kepemimpinan Digital dalam meningkatkan kinerja organisasi peran Teknologi Informasi dan Komunikasi - Sri Maryati; Muhammad Ichsan Siregar (Politeknik Ganesha Medan, 2022)
This study aims to examine the role of Information Communication of Technology (ICT) innovation on the relationship between leadership factors and organization performance. Although studies related to Information Communication of Technology have been carried out, there has been no research related to Information Communication of Technology with company performance. Given the rapid development of technology, it demands a change in business strategy to respond to the needs of organizations to be more innovative through technology. This research contributes to SMEs to be more adaptive in responding to developments in technology through innovation by applying ICT to improve organizational performance.Digitalization is needed as an effort to change the direction of the organization's perspective and market response. As technology develops rapidly, it demands changes in business strategy to respond to organizational needs through technology. This research is a quantitative study, using primary data obtained through questionnaires, using purposive sampling method. This research was conducted on SMEs in the city of Palembang. Then the data were analyzed using SEM-PLS to test the mediation effect using WarpPLS.7.0. based on the results of the analysis leadership has an influence on organizational performance and Innovation Information Communication of Technology (ICT) mediates the relationship of leadership to organizational performance. This research contributes to SMEs to be more adaptable in responding to developments in technology through innovation by applying Information Communication of Technology (ICT) to improve organizational performance.